Assessing the Influence of Water Constituents on the Radiative Heating of Laptev Sea Shelf Waters - Soppa, Mariana A.; Pefanis, Vasileios; Hellmann, Sebastian; Losa, Svetlana N.; Hölemann, Jens; Martynov, Fedor; Heim, Birgit; Janout, Markus A.; Dinter, Tilman; Rozanov, Vladimir; Bracher, Astrid (Frontiers in Marine Science, 2019)
The presence of optically active water constituents is known to attenuate the light penetration in the ocean and impact the ocean heat content. Here, we investigate the influence of coloured dissolved organic matter (CDOM) and total suspended matter (TSM) on the radiative heating of the Laptev Sea shelf waters. The Laptev Sea region is heavily influenced by the Lena River, one of the largest river systems in the Arctic region. We simulate the radiative heating by using a coupled atmosphere-ocean radiative transfer model (RTM) and in situ measurements from the TRANSDRIFT XVII expedition carried out in September 2010. The results indicate that CDOM and TSM have significant influence on the energy budget of the Laptev Sea shelf waters, absorbing most of the solar energy in the first \replaced{two meters}{2 m} of the water column. In the station with the highest CDOM absorption (aCDOM(443) = 1.77 m-1) \replaced{$\sim$43}{42.6}% more energy is absorbed in the surface layer compared to the station with the lowest aCDOM(443) ($\sim$0.2 m-1), which translates to an increased \replaced{radiative}{radiant} heating rate of \replaced{$\sim$0.6}{0.57}°C\deleted[remark=]{/day}. The increased absorbed energy by the water constituents also implies in increased sea ice melt rate and changes in the surface heat fluxes to the atmosphere. By \replaced{using}{combining} satellite remote sensing and RTM we \replaced{quantify}{present} the spatial distribution of the radiative heating in the Laptev Sea for a typical summer day. The tools developed here \added[remark=]{(the combined use of satellite remote sensing, RT modeling and in situ observations)} and tested in our case study can be used to improve the parameterizations of coupled atmosphere-ocean models to assess the \replaced{role}{feedback} of the ocean \added[remark=]{in the effect of} Arctic \replaced{a}{A}mplification.